The Relationship Of Family Support To The Self-Care Independence Of Children With Mental Retardation In SLB Negeri Subang - Susan Nuramelia Sari; Habsyah S Agustina; Ade Nuraeni (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Mental retardation is an intellectual disorder that is generally characterized by mental abilities or intelligence that feels below average. Self-care is indispensable for children with disabilities who find it challenging to carry out activities. The purpose of this study is to analyze the relationship of family support to the independence of self-care for mentally disabled children in SLB Negeri Subang. This study is a type of quantitative correlation research design that uses cross-sectional analysis. The sample in this study was 60 respondents from parents of mentally disabled children with purposive sampling techniques. Data collection used family support and self-care independence questionnaires and data analysis using the Chi-Square test. The study results showed that most respondents had the criteria of low-income family support (68.3%) and most self-care independence (65.0%). In addition, the results of the Chi-Square statistical test show p=0.000 < 0.05. The conclusion is that there is a relationship between family support and the independence of self-care for mentally disabled children in SLB Negeri Subang. So it is hoped that families can provide and increase good support for children with mental retardation by providing informational, emotional, judgmental, and instrumental support.